Tricholeiperia peruensis n. sp. (Nematoda, Molineidae) from Lophostoma silvicolum occidentalis (Chiroptera, Phyllostomidae) in Tumbes, Peru - Vargas, Marina (2008)
In the present work, Tricholeiperia peruensis. n sp. (Nematoda, Molineidae) is described on the basis of 25 collected specimens from 5 bat intestines of the Lophostoma silvicolum occidentalis species from Angostura, district of Pampas de Hospital, department of Tumbes, Peru. The new species is characterized by the morphology of the cephalic vesicle in the form of hood with recesses, for the size and form of spikes whose distal end of the external branch is divided in 2 from which the internal branch undergoes a new division; by the disposition of the ribs of the copulatory apparatus where, among others details, the pre- and post ventral ribs are separated and the external-dorsal ribs begin near the half of the dorsal trunk and are heavy.